GAMBARAN DETERMINASI DIRI PADA PEREMPUAN DI DUNIA POLITIK (STUDI KASUS DPRK KOTA BANDA ACEH DAN KABUPATEN ACEH BESAR) - Juli Andriyani; Siti Hajar Hidayati (Pusat Studi Wanita UIN Ar-Raniry, 2021)
The existence of women in politics is needed as a representation of women's voices to influence political policy. There are several factors that influence the presence of women in the political world such as participation in party activities, ideology of the party chosen, social support, educational background and political experience. It requires strong determination to compete in political participation. One psychological theory that discusses self-determination is the theory of self-determination. There are three parts in the theory of self-determination, namely the need for competence, interrelation and autonomy. Based on this explanation, this study aims to see a picture of self-determination in Aceh women in the political world. The study uses qualitative methods with purposive sampling technique. The sample of the study was a female councilor in the DPRK. Data collection is done by interview and observation. The results showed that all three parts of the theory of self-determination were found in women councilors in the DPRK Banda Aceh City and Aceh Besar District. Self-determination is an internal factor that makes female legislators able to survive and adapt well in the political world.There are also supporting external factors such as family factors, which are dominantly active in the political world.